Aeroelastic response and energy harvesting from a cantilevered piezoelectric laminated plate. (January 2018) - Tang, D.M.; Dowell, E.H.
Abstract: A new nonlinear computational model and code for a piezoelectric–aeroelastic coupled system has been developed. A cantilevered piezoelectric laminated plate in yawed flow ( β ≤ 9 0 0 ) and inverted yawed flow ( β > 9 0 0 ) with a rotated vortex lattice aerodynamic model and new inextensible beam and plate theory is considered in this computational model. For the linear piezoelectric–aeroelastic model a critical flutter or a divergence phenomenon is found for yaw angles β ≤ 9 0 0 or β > 9 0 0 respectively. The divergence speed is independent of the piezoelectric force. Beyond the linear flutter speed, a limit cycle oscillation (LCO) was found for β ≤ 9 0 0 and a large static deflection has been observed for β > 9 0 0 . The power extraction from the piezoelectric network depends on the LCO amplitude, the LCO mode shape and the resistive load, R, for β ≤ 9 0 0 . As flow velocity and resistive load increase, the power extraction increases. From a power efficiency analysis, the best power efficiency is found for a flag like plate when β = 0 0 . This is because this configuration provides the largest LCO amplitude and the best LCO mode shape with a larger bending curvature.